Translation Accuracy of English Idiomatic Expression into Indonesian in Soul Film Subtitle by Disney+ Retail - Rizka Nuraini; Dr. Frans Sayogie, M.Pd (TALENTA, 2024)
The difficulty of translating idiomatic expressions arises when there is no direct equivalent between the source and target languages. In order to discover how translators deal with those issues, this study aims to identify types of idiomatic expressions and examine the accuracy of Soul film subtitle with the inspection of strategies used by the translator. This study used a qualitative descriptive method by applying the classification of idioms based on McCarthy and O’dell’s theory, the strategy in translating idioms by Mona Baker, and the translation accuracy level by Nababan. The data was gathered by watching the film, reading the subtitles, and noting the idiomatic expressions present in the film. This study took 14 samples to be analyzed from the 98 data found in the source text. From all data, there are 8 types of idioms which are verb + object, prepositional phrases, compound, simile/simili, binomial, whole clause/sentence, cliché/fixed statements, and euphemisms. The translator used 5 strategies in translating the idioms which are using an idiom of similar meaning and form, using an idiom of similar meaning but dissimilar form, translation by paraphrase, translation by omitting the play of the idiom, and translation by omitting the entire idiom. As for the accuracy, this study found 94 data of accurate translation, 2 translations of almost accurate, and 2 translations not accurate. However, it can be concluded that the translation has a high-level accuracy making the quality of the translated idioms in the subtitle is good, although it can be still improved. Keyword: Idiomatic expressions, translation strategy, and accuracy level